Does Perceived Impact of Change Affect Readiness for Change in Higher Education Governance? - Erlyani, Neka; Suhariadi, Fendy; Ardi, Rahkman (International Journal Labs, 2023)
Background: Changes in the financial governance status of more autonomous state universities require readiness for change in the management of state universities. Academic staff is an HR group that carries out administrative tasks in the state university’s management. The first factor of readiness for change individuals must have is to know that change will be beneficial for themselves and the organization. Aim: This study aims to determine the role of perceived impact of change on readiness for change in academic staff. Method: This research is a quantitative study with 254 subjects selected using Holt’s RFCQ adaptation scale and Vakola’s perceived impact of change adaptation scale as research instruments. The data were analyzed using a simple linear regression analysis technique via IBM SPSS. Findings: Perceived impact of change is proven to affect readiness for change in academic staff. If members perceive that change is positive and beneficial for themselves and their organization, they will be more ready to accept change. In addition, demographic factors have no effect on readiness for change.